“Living in an Alter World:” Pagsusuri sa Pagtatanghal ng Sarili at Pook-Pangkabuhayan ng mga Alter sa Mundo ng X (Dating Twitter) (“Living in an Alter World:” An Analysis of Self-Presentation and Livelihood Spaces of “Alter” Users on X (formerly Twitter) - Dumaraos, Tracy Valerie; Reyes, Ryan; Liwanag, Leslie Anne (Social Sciences and Development Review, 2024)
X (formerly Twitter) is among the top five most utilized social media services in the Philippines. It serves as one of the most prolific virtual communities for the LGBTQIA+ community (Statista, 2022). Unknown to many, the Alterverse community in X was created because of the need for many gay males to freely express themselves on a particular platform. Using content analysis with the intention of studying specific groups, such as the Alters of X as social media users, this paper probes the current state of the Alter world after COVID-19. It was discovered in the study that the alter world is not exclusive to gays because of the varied presence of heterosexual content creators, resulting in the design of alter accounts exhibiting a different feature. The study shows that self-expression is the primary reason homosexual content creators establish alter accounts, whereas providing service using oneself in exchange for financial gains is the primary aim of heterosexual alter content creators.From this paper, it is evident that there is a presence of both homosexual and heterosexual content creators in the world of Alterverse in X. However, while both display similar actions, they differ in their goals. This result may be used in a deeper study on the lives of Alters.
Keywords: alter; lgbtqia+; social media; sex industry; self-expression